Los defectos observables y la garantía de buen funcionamiento en la compraventa. (2014)
This paper discusses two legal mechanisms for buyer´s protection contained in the Colombian Commercial Code, parallel to building regulations, because of hidden defects in the sale, which are: guarantee by observable defects at delivery and guarantee for proper functioning. The author analyzes the poor way such actions are enshrined in the Code as a consequence of a fragmented and dispersed regime for defective compliance actions in the laws of Private Law. This paper proposes a reinterpretation of such actions from the perspective of the lack of conformity that is based on a unified system of remedies for breach, concepts embodied in modern instruments of contract law.